Mediastinal cryobiopsy for pathological diagnosis of fibrosing mediastinitis-associated pulmonary hypertension - You, Ya-Ting; Zuo, Hao; Li, Jing-Meng; Zhu, Xian-Bo; Zhang, Jing; Fu, Wan-Lei; Huang, Zan-Sheng; Herth, Felix; Fan, Ye (Respiration, 2024)
Introduction: Fibrosing mediastinitis is a benign but fatal disorder characterized by the proliferation of fibrous tissue in the mediastinum, causing encasement of mediastinal organs and extrinsic compression of adjacent bronchovascular structures. FM-associated pulmonary hypertension (FM-PH) is a serious complication of FM, resulting from the external compression of lung vessels. Pathologic assessment is important for etiologic diagnosis and effective treatment of this disease. Case Presentation: A 59-year-old male patient presented at our hospital and was diagnosed with FM-PH. He declined surgical biopsy that is the reference standard for pathologic assessment, in consideration of the potential risks. Therefore, an endobronchial ultrasound examination was performed, which identified the subcarinal lesion. Under ultrasound guidance, four needle aspirations were carried out, followed by one cryobiopsy. Histopathological examination of transbronchial needle aspiration specimens was inconclusive, while samples from cryobiopsy suggested a diagnosis of idiopathic FM. Further immunophenotyping demonstrated the infiltration of lymphocytes, macrophages, and FOXP3-positive cells in FM-PH. Conclusion: Mediastinal cryobiopsy might be a novel and safe option for FM-PH patients who are unwilling or unsuitable for surgical procedure.
Online veröffentlicht: 25. Januar 2024
Gesehen am 11.06.2024